In search of a better life: The occupational attainment of rural and urban migrants in China - Ayako Kondo; Dongshu Ou (Osaka University, Institute of Social and Economic Research (ISER), 2010)
This paper investigates the occupational attainment and job mobility of permanent ruralto-urban migrants and compares them with migrants who were born with an urban hukou. Using data from the 2003 China General Social Survey, we examine how much of the gaps in occupational-prestige scores between rural- and urban-born migrants can be explained by differences in observable characteristics up to the time of migration. We find that, with controls for these characteristics, the difference in occupational attainment between rural and urban migrants becomes statistically insignificant or even positive for some subgroups. In contrast, our analysis of job mobility reveals that rural migrants are generally more mobile and also more likely to move to better jobs by changing workunits, whereas urban migrants are more likely to be promoted within a work-unit.
Keywords: O15; J0; J61; J62; 330; internal migration; China; job mobility; occupational prestige; hukou; Landflucht; Soziale Lage; Beruf; Reputation; Arbeitsmobilität; China